2013
DOI: 10.12871/00039829201314
|View full text |Cite
|
Sign up to set email alerts
|

Role of CREB signaling in aging brain

Abstract: During aging, brain undergoes several changes which influence its function through alteration in the expression of genes. Some of these genes are regulated by estrogen which requires a host of coregulator proteins including CREB. In brain, CREB is expressed in different regions and regulates a wide range of functions such as cellular growth, proliferation and memory in response to a variety of intracellular signaling events including synaptic efficacy and long-lasting changes in synaptic plasticity. In respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…40 Previous studies of CREB focused predominantly on its role in neuroprotection. 41 Activation of CREB is a well-known protective mechanism against cerebral ischemic injury. 42 Recently, CREB in cardiac protection has garnered significant interest.…”
Section: Discussionmentioning
confidence: 99%
“…40 Previous studies of CREB focused predominantly on its role in neuroprotection. 41 Activation of CREB is a well-known protective mechanism against cerebral ischemic injury. 42 Recently, CREB in cardiac protection has garnered significant interest.…”
Section: Discussionmentioning
confidence: 99%
“…59 Nevertheless, alterations in CREB signaling can contribute to cognitive impairment 61 and may lead to increased incidence and progression of neurodegenerative diseases such as Huntington's, Alzheimer's, and Parkinson's disease. 62,63 Defects in Synaptic Plasticity May Reflect Altered Mitochondrial Function…”
Section: Activation Of Ltp Signalingmentioning
confidence: 99%
“…CREB1, CAMP responsive element binding protein 1, is a protein that binds the cAMP response element and regulates transcription. Its expression and function can modulate oxidative stress-induced senescence in granulosa cells by reducing the mitochondrial function [ 85 ] and CREB signaling has been related to lung and brain aging [ 86 , 87 ]. Finally, EIF5A2 encoding for the Eukaryotic Initiation Factor 5A2, plays a key role in the regulation of protein translation, and it has been reported that, in transgenic mice, its overexpression enhances the aging process [ 88 ].…”
Section: Discussionmentioning
confidence: 99%